ShRNA-Targeted COMMD7 Suppresses Hepatocellular Carcinoma Growth - Zheng, Lu; Liang, Ping; Li, Jing; Huang, Xiao-bing; Liu, Shi-cheng; Zhao, Hong-zhi; Han, Ke-qiang; Wang, Zheng (PLOS ONE, 2012)
Background COMMD7 is a newly identified gene overexpressed in hepatocellular carcinoma (HCC) and associated with tumor invasion and poor prognosis. We aim to examine the biological function of COMMD7 in HCC by shRNA silencing. Methods COMMD7 expressions were examined in human HCC cell lines HepG2, Huh7, Hep3B, HLE, HLF, SK-Hep-1 and PLC/PRF/5 cells. Recombinant pGenesil-COMMD7-shRNA was transfected into COMMD7-abundant HepG2 cells to silence COMMD7 expression. The effects of COMMD7 silencing on HepG2 cell proliferation in vitro and xenograft tumor growth in vivo were evaluated. Flow cytometry profiling was used to detect the presence of apoptosis in COMMD7-silenced HepG2 cells and to differentiate cell cycle distribution. Electrophoretic mobility shift assay and luciferase reporter assays to examine the activities of nuclear factor-kappaB (NF-κB) signaling pathways in response to tumor necrosis factor (TNF)-α in COMMD7-silenced HepG2 cells. Results COMMD7 expression level was abundance in HepG2 and SK-Hep-1 cells. COMMD7 was aberrantly overexpressed in HepG2 cells, whilst pGenesil-COMMD7-shRNA exhibited a maximal inhibition rate of 75%. COMMD7 silencing significantly reduced HepG2 cell proliferation and colony formation. The knockdown of COMMD7 resulted in an increased apoptosis and cell cycle arrest at S-phase. COMMD7 knockdown also exhibited an antineoplastic effect in vivo, which manifested as tumor xenograft growth retardation. COMMD7 silencing also suppressed the responsiveness of NF-κB signaling pathway to the stimulation with TNF-α in vitro. Moreover, the similar suppressive effects of COMMD7 silence on SK-Hep-1 cells were also observed. Conclusions COMMD7 contributes to HCC progression by reducing cell apoptosis and overcoming cell cycle arrest. The proliferative and antiapoptotic effects of COMMD7 may be mediated by NF-κB signaling pathway.